Biosphere Origin and Evolution - Dobretsov, Nikolay; Kolchanov, Nikolay; Rozanov, Alexey; Zavarzin, Georgy (Springer US : Imprint: Springer, 2008)
Modern natural science shows that the infancy of life on Earth experienced prebiotic evolution and included the emergence of primitive self-reproducing biologic forms and their systems. The subsequent coevolution of inorganic environment and biologic systems resulted in global propagation of life over the Earth and its enormous diversification. Diverse living organisms colonized the land, water, and atmosphere, as well as upper layers of the lithosphere, thereby forming the biosphere. The book covers notions by scientists of various branches on the evolutionary relationship between the biosphere and geosphere, evolution features at various levels of living matter organization, and problems of prebiotic evolution and life origin. The data were collected in the course of the RAS program "Biosphere origin and evolution" (subprogram II) in 2003-2006. The objectives of this subprogram were (1) generalization of data related to problems of biosphere origin and evolution accumulated by geneticists, molecular biologists, zoologists, botanists, paleontologists, microbiologists, geologists, chemists, and archaeologists; (2) search for new interdisciplinary approaches to biosphere origin and evolution; (3) development of a "lingua franca" understandable by experts in various fields, which would allow apprehension of results concerning the topic obtained in allied sciences.